Teknik Marketing Plan Stasiun Televisi Berdasarkan Viewers Values dan Acuan Produksi Acara - Anung Rachman (Institut Seni Indonesia Surakarta, 2007)
Rivalries among national and local TV companies have led to strategies and tactics as to how to seize and maintain potential viewers. If a company maintains its potential viewers it will receive increased revenue. If its competitors suceed in grabbing its potential viewers it will be in great loss. It is essential therefore that a television station company see the strategies and tactics utilized by its competitors. The best way is by conducting marketing plan.Keywords : marketing plan, market research, program production, television stationÂ